Elastic bonding coating for preventing aluminum single plate from deforming for thermal insulation decorative integrated panel and preparation method thereof

By using microporous polyurethane elastomer and phase change composite materials, the problem of insufficient rigidity of the bonding layer between the aluminum veneer panel and the insulation core material is solved, the high-temperature rigidity and low-temperature toughness of the polyurethane coating are improved, and the deformation of the aluminum veneer is avoided. Improved decorative effect and safety performance.

CN118271955BActive Publication Date: 2024-12-27JILIN DINGHENG BUILDING MATERIALS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410509322.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2024-12-27
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

The bonding layer of the aluminum veneer panel and the insulation core material of the existing thermal insulation decorative integrated board has a high stiffness and insufficient toughness, which leads to severe deformation of the aluminum veneer, affecting the appearance effect and may lead to peeling of the panel and the insulation core material, cracking of the plate edge, affecting safety. coefficient.

Method used

Microporous polyurethane elastomer is used as the elastic bonding coating. By adjusting the type and molecular weight of the polyol, the cross-linking reaction of the low-foam particles of polyamide 1212 elastomer and diisocyanate is formed to form a support body, reduce the density of polyurethane and increase the bearing capacity. and elastic, and use phase change composite materials to adjust the influence of temperature fluctuations, prepare elastic bonding coatings that prevent aluminum veneer deformation.

Benefits of technology

The high-temperature rigidity and low-temperature toughness of the polyurethane elastic coating are improved, the bearing capacity and shape stability of the polyurethane are enhanced, deformation problems caused by temperature fluctuations are avoided, and the decorative effect and safety performance of aluminum veneers are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004811278300000061
    Figure BDA0004811278300000061
  • Figure BDA0004811278300000071
    Figure BDA0004811278300000071
  • Figure BDA0004811278300000081
    Figure BDA0004811278300000081
Patent Text Reader

Abstract

The invention discloses an elastic bonding coating for preventing aluminum veneer deformation of a thermal insulation decorative integrated panel and a preparation method thereof. The coating comprises a component A and a component B, wherein the component A comprises the following raw materials in parts by mass: 75 parts of polyol, 5 parts of catalyst, 4 parts of surfactant, 2 parts of foaming agent, 15 parts of flame retardant and 1 to 20 parts of polyamide 1212 elastomer low-foam particles; the component B comprises the following raw materials in parts by mass: 30 to 70 parts of crude MDI and 10 parts of phase change composite material; the elastic coating is sprayed on the back of the aluminum veneer and has the advantages of good wear resistance, corrosion resistance, high toughness, high resilience, aging resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane, and in particular to an elastic bonding coating used for a thermal insulation decorative integrated panel to prevent aluminum single plate from deforming, and a preparation method thereof. Background Art

[0002] The weight of the thermal insulation decorative integrated board is very light, which greatly reduces the weight load of the building. In addition, the installation process is simple, and the supporting material system is also relatively light. Therefore, the thermal insulation decorative integrated board is very suitable for the exterior wall decoration of the building. The thermal insulation decorative integrated board has a flat surface, which is simpler than the traditional thermal insulation method and has a better thermal insulation effect, far superior to the ordinary and traditional thermal insulation method. In the actual application of the product, the thermal insulation core material is used as the intermediate of the thermal insulation decorative integrated board to play a role in thermal insulation. At present, a high-strength adhesive layer is used to bond the thermal insulation core material and the decorative panel, or rivets are used to fix it to prevent peeling and falling off.

[0003] The applicant is Zheng Lihua, and the invention patent with patent number ZL201220001205.8 discloses a rock wool thermal insulation decorative integrated panel. The above-mentioned rock wool thermal insulation material decorative integrated panel includes a base plate, an insulation layer, a rigid carrier and a finishing layer; the base plate is an inorganic composite board; the insulation layer is a rock wool filling material that is self-adhesive by brushing glue to form an insulation material, one side of which is bonded and fixed to the base plate through an adhesive layer, and the other side is bonded and fixed to one side of the rigid carrier through an adhesive layer; the finishing layer is arranged on the other side of the rigid carrier.

[0004] The applicant is Ke Gaojie. The invention patent with patent number ZL201921246830.7 discloses an integrated insulation and decorative panel system, which at least includes an interface force bridge layer, an adhesive layer, a sealing layer, an insulation layer and a finishing layer. The interface force bridge layer bonds the original decorative surface of the wall and the adhesive layer through bidirectional penetration. The adhesive layer is arranged between the interface force bridge layer and the sealing layer. The sealing layer is successively composed of an insulation layer and a finishing layer on the side facing away from the adhesive layer. The sealing layer is composed of silicone sealant and foam strips. The sealing layer and the insulation layer are fixedly connected by anchors.

[0005] The thermal insulation decorative integrated board has high fireproof performance. The thermal insulation layer, carrier layer and structural adhesive are all non-flammable. This product has the advantages of beautiful decoration, thermal insulation and energy saving, simple construction and ultra-long service life. It can be produced according to industrial standards and has a short production cycle. It not only has super flexibility, but also increases the cleanliness of the surface and effectively prevents the generation of color difference.

[0006] In the prior art, the decorative panel of the integrated board usually uses an adhesive layer with high strength adhesion to bond the thermal insulation core material and the decorative panel; such operation easily leads to the bonding layer between the aluminum veneer panel and the thermal insulation core material being high in rigidity but insufficient in toughness, thus causing serious deformation of the aluminum veneer, seriously affecting the appearance effect. In severe cases, the panel and the thermal insulation core material may peel off, or even the edge of the panel may crack, affecting the safety factor of the thermal insulation decorative integrated board. Summary of the invention

[0007] At present, microporous polyurethane elastomer, as a special polyurethane foam material, has the advantages of good wear resistance, corrosion resistance, high toughness, high resilience, aging resistance, etc. At the same time, this material has a simple production process, high production efficiency, low production cost, and the formula can be flexibly designed. The adjustable space of product performance is large, and it has a very broad application prospect.

[0008] Microporous polyurethane elastomer can be regarded as a block polymer as a whole, which is composed of hard segments and soft segments. Therefore, microporous polyurethane elastomer has the characteristics of low temperature compliance and high resilience, as well as certain rigidity and strength. Different polyols constitute the soft segment of the material, and the effect of different polyols on the performance of microporous polyurethane elastomer is the effect of the soft segment in the microphase structure on the material performance. Different polyols have different compositions, such as different molecular weights, different molecular structures, different functionalities, etc. Therefore, the macromolecular chains produced after the chain growth reaction with isocyanate will be different in molecular chain length, structure, etc., which will affect the overall performance of microporous polyurethane elastomer. By cross-linking the polyamide 1212 elastomer low-foam particles with diisocyanate during foaming, the polyamide 1212 elastomer low-foam particles form a support in the polyurethane foam, which not only reduces the density of polyurethane, but also enhances the load-bearing and elasticity of polyurethane. By adjusting the composition and proportion of the two-component raw materials of the reaction, the added polyamide 1212 elastomer low-foam particles and phase change materials are used as heat-absorbing materials to absorb heat and control the deformation of the elastic coating due to overcooling and overheating, thereby avoiding large fluctuations in coating performance with temperature.

[0009] The elastic bonding coating used for thermal insulation decorative integrated panels to prevent aluminum veneer deformation is composed of component A and component B, wherein component A includes the following raw materials in parts by mass: 75 parts of polyol, 5 parts of catalyst, 4 parts of surfactant, 2 parts of foaming agent, 15 parts of flame retardant and 1-20 parts of polyamide 1212 elastomer low-foam particles; and component B includes the following raw materials in parts by mass: 30-70 parts of crude polymer MDI and 10 parts of phase change composite materials.

[0010] The preparation method of the elastic bonding coating for preventing the deformation of the aluminum single plate of the thermal insulation decorative integrated plate comprises the following steps:

[0011] S1: Stirring polyol, catalyst, surfactant, foaming agent, flame retardant and polyamide 1212 elastomer low-foam particles for 1 to 2 hours to obtain component A;

[0012] S2: Mix the polymerized MDI and the phase change composite material and stir for 1 to 1.5 hours to obtain component B;

[0013] S3: Mix component A and component B, stir at high speed to make them evenly mixed, spray them on the back of the aluminum veneer, adhere the thermal insulation core material after reaching the specified thickness, and further assemble the thermal insulation decorative integrated panel.

[0014] Preferably, the catalyst is a mixture of one or more of bis(dimethylaminoethyl) ether catalyst and triethylenediamine.

[0015] Preferably, the polyol is a mixture of one or more of polyoxytetramethylene ether diol with a molecular weight of 2000, polycaprolactone diol with a molecular weight of 2000, and polyoxypropylene ether diol with a molecular weight of 2000.

[0016] Preferably, the catalyst is a mixture of one or more of bis(dimethylaminoethyl) ether catalyst and triethylenediamine.

[0017] Preferably, the surfactant is a mixture of one or more of Tween-80, sodium dodecylbenzene sulfonate, silicone oil 8860, polyoxyethylene laurate, and polyoxyethylene lauryl alcohol ether.

[0018] Preferably, the blowing agent is a mixture of one or more of water, PU-88, pentane and HCFC-141b.

[0019] Preferably, the flame retardant is a mixture of one or more of aluminum hydroxide, magnesium hydroxide, zinc borate, antimony trioxide, colloidal antimony pentoxide, sodium antimony, tri(2-carbonylethyl)phosphine hydrochloride, tri(1-chloro-2-propyl) phosphate, ammonium polyphosphate, silicone flame retardant, expandable graphite, and dihydroxy metal oxide.

[0020] Preferably, the crude MDI is a polyisocyanate.

[0021] Preferably, the phase change composite material comprises the following raw materials in parts by mass: 80 parts of high-density polyethylene, 20 parts of maleic anhydride grafted polyethylene, 100 parts of polyethylene glycol with a molecular weight of 10,000, 5 parts of RT110 paraffin, 10 parts of erythritol, 15 parts of graphite powder, 3 parts of polyvinyl pyrrolidone and 0.5 parts of antioxidant.

[0022] Preferably, the polyamide 1212 elastomer low-foam particles include the following raw materials in parts by mass: 100 parts of nylon 1212 salt, 5 to 10 parts of dodecanedioic acid, and 30 to 90 parts of polybutylene glycol.

[0023] Preferably, the preparation method of the polyamide 1212 elastomer low-foam particles is:

[0024] First, dodecanedioic acid and dodecanediamine were dissolved in ethanol at 55-65°C, stirred for 1 hour, and then the ethanol was filtered to obtain nylon 1212 salt, which was then dried in a vacuum oven for later use;

[0025] Add the dried nylon 1212 salt and dodecanedioic acid into the autoclave, fill the autoclave with nitrogen, heat the autoclave to 120°C, stir continuously, heat to 220°C after 30 minutes, keep the temperature and pressure for 1.5 hours, release the pressure in the autoclave and raise the temperature in the autoclave to 260°C; react for about 1 hour, add polybutylene glycol with a molecular weight of 2000 into the autoclave, and then add 1 to 3 parts of tetrabutyl titanate to promote esterification reaction, and the reaction is carried out at 280°C and a pressure of 1000Pa for 3 hours to obtain a polyamide 1212 elastomer;

[0026] Place the polyamide 1212 elastomer in an autoclave equipped with a heating jacket and a temperature controller. After replacing the air in the autoclave with CO2 fluid, fill the autoclave with CO2 to reach a pressure of 15 MPa and heat to 160-180°C. Keep the temperature and pressure for 2 hours, and quickly reduce the pressure to ambient pressure to obtain a polyamide 1212 elastomer low-foam material, which is then crushed to obtain polyamide 1212 elastomer low-foam particles.

[0027] The present invention discloses the following technical effects:

[0028] (1) Adjust the type and molecular weight of the polyol in the formula to determine the effect on the performance of the microporous polyurethane elastomer; while reducing the cost of polyurethane foam, by controlling low foaming, the defects of the polyurethane after the elastic coating foaming, such as poor bearing capacity, large compression deformation, easy deformation under long-term load, and difficulty in recovery, can be solved.

[0029] (2) The present invention provides hydroxyl groups on the surface of polyamide 1212 elastomer low-foam particles, which are easily dispersed in polyurethane stock solution, especially the hydroxyl groups on the particle surface can react with diisocyanate to form interface defects due to polyurethane foaming. The polyamide 1212 elastomer low-foam particles have high toughness, high resilience, and high strength, thereby increasing the high-temperature rigidity and low-temperature toughness of the polyurethane elastic coating.

[0030] (3) The present invention provides a phase change composite material, which is made of high-density polyethylene, maleic anhydride grafted polyethylene, molecular weight 10000 polyethylene glycol, RT110 paraffin, erythritol, graphite powder, polyvinyl pyrrolidone and antioxidant as raw materials, mixed evenly and added into a twin-screw extruder for extrusion granulation. The phase change composite material has very high mechanical strength and elastic modulus, and two phase transition temperatures of 40°C and a high-temperature phase transition temperature of 120°C appear at the same time, which can better regulate the adverse effects caused by excessive temperature fluctuations of the coating in summer. DETAILED DESCRIPTION

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0032] The parts of the present invention, unless otherwise specified, are all calculated by mass.

[0033] The preparation method of polyamide 1212 elastomer low foam particles is as follows:

[0034] First, dodecanedioic acid and dodecanediamine were dissolved in ethanol at 55-65°C, stirred for 1 hour, and then the ethanol was filtered to obtain nylon 1212 salt, which was then dried in a vacuum oven for later use;

[0035] Add the dried nylon 1212 salt and dodecanedioic acid into the autoclave, fill the autoclave with nitrogen, heat the autoclave to 120°C, stir continuously, heat to 220°C after 30 minutes, keep the temperature and pressure for 1.5 hours, release the pressure in the autoclave and raise the temperature in the autoclave to 260°C; react for about 1 hour, add polybutylene glycol with a molecular weight of 2000 into the autoclave, and then add 1 to 3 parts of tetrabutyl titanate to promote esterification reaction, and the reaction is carried out at 280°C and a pressure of 1000Pa for 3 hours to obtain a polyamide 1212 elastomer;

[0036] Place the polyamide 1212 elastomer in an autoclave equipped with a heating jacket and a temperature controller. After replacing the air in the autoclave with CO2 fluid, fill the autoclave with CO2 to reach a pressure of 15 MPa and heat to 160-180°C. Keep the temperature and pressure for 2 hours, and quickly reduce the pressure to ambient pressure to obtain a polyamide 1212 elastomer low-foam material, which is then crushed to obtain polyamide 1212 elastomer low-foam particles.

[0037] The performance is shown in Table 1.

[0038] Table 1:

[0039]

[0040]

[0041] The mechanical properties of polyamide 1212 elastomer are segmented block copolymers, which play a decisive role in the process conditions of extrusion and injection molding. They are usually affected by the ratio of soft and hard segments in the polymer, chemical composition, relative molecular weight distribution, and synthesis method. Through the analysis of tensile strength and elongation at break, when the content of dodecanedioic acid is added to 5 parts, the terminal carboxylic acid content is insufficient during the polymerization of nylon salt, resulting in insufficient polymerization degree with polybutylene glycol and performance deviation. When the content of dodecanedioic acid is added to 7.5 parts, the terminal carboxylic acid content is greatly increased during the polymerization of nylon salt, resulting in an increase in the degree of polymerization with polybutylene glycol and improved performance. When the content of dodecanedioic acid is added to 10 parts, the residual free carboxylic acid content increases during the polymerization of nylon salt, resulting in the appearance of small molecular weight oligomers when polymerized with polybutylene glycol, and performance deviation. Comprehensive analysis shows that the product obtained by adding 7.5 parts of dodecanedioic acid to nylon salt and adding 60 parts of butanediol to polymerize has the best performance.

[0042] This experiment uses full water foaming, and selects different types of polyols with a molecular weight of 2000 and a functionality of 2, namely polyoxytetramethylene ether diol, polycaprolactone diol, and polyoxypropylene ether diol, which react with polyisocyanate (MDI) respectively, and use bis (dimethylaminoethyl) ether and triethylenediamine as catalysts. By adjusting the isocyanate index R of the two to 1.1, the gel reaction is controlled to make a polyurethane elastomer, in order to study the effects of these three raw materials on the various properties of the polyurethane elastomer, see Table 2.

[0043] Table 2

[0044]

[0045] From Table 2, it can be seen that the physical and mechanical properties of polyurethane elastomers synthesized from four different polyols are different. Polyoxytetramethylene ether diol and polyoxypropylene ether diol have ether bonds with good flexibility on their molecular chains. The segments in the molecular chains are easier to move, which makes the material have better flexibility and thus better rebound performance. Because the main chain of the polyoxypropylene ether diol molecular chain contains side methyl groups, the arrangement between the molecular chains is not tight enough, while the molecular chain of polyoxytetramethylene ether diol has more regularly arranged methylene groups, and the molecular chain is arranged in an orderly manner, which is more conducive to crystallization, and the degree of crystallization is greater than that of polyoxypropylene ether diol type polyurethane elastomer. It is precisely because of the existence of the crystal region that the hardness, tensile strength and elongation at break of the material are improved, which also makes the physical and mechanical properties of polyoxytetramethylene ether diol type microporous polyurethane elastomer better than those of polyoxypropylene ether diol type polyurethane elastomer.

[0046] Polycaprolactone diol is a polyester polyol. There are ester groups with strong polarity between their molecular chains, which enhances the mutual attraction between the molecular chains. Because polyurethane elastomers are composed of alternating soft segments and hard segments, the strong relative attraction between the molecular chains will form a large number of hydrogen bonds between the soft segments and the hard segments, which in turn promotes the interaction between the molecules, so that the material has higher tensile strength and elongation at break. It can also be seen from the table that the tensile strength of polyester materials is significantly better than that of polyether materials. The ball rebound performance of polyester materials is not as good as that of polyether materials. This is because the interaction between the molecular chains greatly restricts the movement of the molecular chains, which reduces the compliance of the material and thus makes the impact rebound performance worse.

[0047] Comprehensive analysis shows that polyoxytetramethylene ether diol type polyurethane elastomer has the best product performance.

[0048] The technical solution of the present invention is further illustrated by the following embodiments.

[0049] Example 1

[0050] An elastic bonding coating for preventing aluminum veneer deformation of a thermal insulation decorative integrated panel is composed of component A and component B, wherein component A includes the following raw materials by weight: 75 parts of 2000 molecular weight polyoxytetramethylene ether diol, 3 parts of bis(dimethylaminoethyl) ether catalyst, 2 parts of triethylenediamine catalyst, 4 parts of silicone oil 8860 surfactant, 2 parts of water, 15 parts of aluminum hydroxide flame retardant and 5 parts of polyamide 1212 elastomer low-foam particles; wherein component B includes the following raw materials by weight: 50 parts of crude polymerized MDI and 10 parts of phase change composite material;

[0051] The phase change composite material includes the following raw materials in parts by mass: 80 parts of high-density polyethylene, 20 parts of maleic anhydride grafted polyethylene, 100 parts of polyethylene glycol with a molecular weight of 10,000, 5 parts of RT110 paraffin, 10 parts of erythritol, 15 parts of graphite powder, 3 parts of polyvinyl pyrrolidone and 0.5 parts of antioxidant.

[0052] The preparation method of the elastic bonding coating for preventing the deformation of the aluminum single plate of the thermal insulation decorative integrated plate comprises the following steps:

[0053] S1: Stirring polyol, catalyst, surfactant, foaming agent, flame retardant and polyamide 1212 elastomer low-foam particles for 1 to 2 hours to obtain component A;

[0054] S2: Mix the crude polymerized MDI and the phase change composite material and stir for 1 to 1.5 hours to obtain component B;

[0055] S3: Mix component A and component B, stir at high speed to make them evenly mixed, spray them on the back of the aluminum veneer, adhere the thermal insulation core material after reaching the specified thickness, and further assemble the thermal insulation decorative integrated panel.

[0056] Preferably, the catalyst is a mixture of one or more of bis(dimethylaminoethyl) ether catalyst and triethylenediamine.

[0057] The polyamide 1212 elastomer low-foam particles include the following raw materials by weight: 100 parts of nylon 1212 salt, 7.5 parts of dodecanedioic acid, and 60 parts of polybutylene glycol;

[0058] First, dodecanedioic acid and dodecanediamine are dissolved in ethanol at 55-65° C., and after stirring for 1 hour, the ethanol is filtered to obtain 100 parts of nylon 1212 salt, which is placed in a vacuum oven for drying;

[0059] Add dried nylon 1212 salt and 7.5 parts of dodecanedioic acid into an autoclave, fill nitrogen into the autoclave, heat the autoclave to 120°C, stir continuously, heat to 220°C after 30 minutes, keep warm and pressure for 1.5 hours, release the pressure in the autoclave and raise the temperature in the autoclave to 260°C; react for about 1 hour, add 80 parts of polybutylene glycol with a molecular weight of 2000 into the autoclave, and then add 1 to 3 parts of tetrabutyl titanate to promote esterification reaction, and the reaction is carried out at 280°C and a pressure of 1000 Pa for 3 hours to obtain a polyamide 1212 elastomer;

[0060] Place the polyamide 1212 elastomer in an autoclave equipped with a heating jacket and a temperature controller. After replacing the air in the autoclave with CO2 fluid, fill the autoclave with CO2 to reach a pressure of 15 MPa and heat to 160-180°C. Keep the temperature and pressure for 2 hours, and quickly reduce the pressure to ambient pressure to obtain a polyamide 1212 elastomer low-foam material, which is then crushed to obtain polyamide 1212 elastomer low-foam particles.

[0061] Example 2

[0062] The addition amount of the polyamide 1212 elastomer low-foam particles in Example 1 was replaced with 10 parts (5 parts in Example 1), and the remaining technical indicators and preparation method were the same as in Example 1 to prepare a low-foam polyurethane elastic coating.

[0063] Example 3

[0064] The addition amount of the polyamide 1212 elastomer low-foam particles in Example 1 was replaced with 15 parts, and the other technical indicators and preparation methods were the same as those in Example 1 to prepare a low-foam polyurethane elastic coating.

[0065] Example 4

[0066] The addition amount of the polyamide 1212 elastomer low-foam particles in Example 1 was replaced with 20 parts, and the other technical indicators and preparation method were the same as those in Example 1 to prepare a low-foam polyurethane elastic coating.

[0067] Example 5

[0068] The amount of crude MDI added in Example 3 was replaced with 30 parts, and the other technical indicators and preparation method were the same as those in Example 3 to prepare a low-foam polyurethane elastic coating.

[0069] Example 6

[0070] The amount of crude MDI added in Example 3 was replaced with 70 parts, and the other technical indicators and preparation method were the same as those in Example 3 to prepare a low-foam polyurethane elastic coating.

[0071] Performance Testing

[0072] The hardness, tensile strength, elongation, tear strength and other properties of the polyurethane elastic coatings prepared in Examples 1 to 6 were tested. The test results are shown in Table 3.

[0073] Table 3

[0074] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Hardness, Shore A 65 69 71 74 63 81 Tensile strength, MPa 9.1 9.4 9.6 9.5 7.8 8.4 Tensile elongation, % 384 401 425 412 364 285 Tear strength, kN / m 9.1 9.7 10.6 10.2 7.5 10.5

[0075] According to Table 3, the polyurethane elastic coatings prepared in Examples 1 to 6 are optimized in hardness, tensile strength, elongation, tear strength and other properties as the content of polyamide 1212 elastomer low-foam particles increases. However, when the content reaches 20 parts, the performance decreases due to the increase in particle interface bonding defects. When the MDI content is too low, the internal reaction is incomplete, causing negative effects, and the performance indicators are generally not high. When the MDI content is too high, the NCO group content is too high, resulting in increased brittleness and decreased elongation, and the performance indicators are generally not high. After comparison, it can be found that the polyurethane elastic coating prepared under the conditions of Example 3 has the best performance.

Claims

1. An elastic bonding coating for preventing aluminum veneer deformation in thermal insulation decorative integrated panels, characterized by: It is composed of component A and component B, wherein component A includes the following raw materials by weight: 75 parts of polyol, 5 parts of catalyst, 4 parts of surfactant, 2 parts of foaming agent, 15 parts of flame retardant and 1-20 parts of polyamide 1212 elastomer low-foam particles; and component B includes the following raw materials by weight: 30-70 parts of crude polymerized MDI and 10 parts of phase change composite material; The polyol is a mixture of one or more of polyoxytetramethylene ether diol with a molecular weight of 2000, polycaprolactone diol with a molecular weight of 2000, and polyoxypropylene ether diol with a molecular weight of 2000; The catalyst is a mixture of one or more of a diether catalyst and triethylenediamine; The phase change composite material comprises the following raw materials by weight: 80 parts of high-density polyethylene, 20 parts of maleic anhydride grafted polyethylene, 100 parts of polyethylene glycol with a molecular weight of 10,000, 5 parts of RT110 paraffin, 10 parts of erythritol, 15 parts of graphite powder, 3 parts of polyvinyl pyrrolidone and 0.5 parts of antioxidant; The preparation method of the polyamide 1212 elastomer low-foam particles is: First, dodecanedioic acid and dodecanediamine were dissolved in ethanol at 55-65°C, stirred for 1 hour, and then the ethanol was filtered to obtain nylon 1212 salt, which was then dried in a vacuum oven for later use; Add the dried nylon 1212 salt and dodecanedioic acid into the autoclave, fill the autoclave with nitrogen, heat the autoclave to 120°C, stir continuously, heat to 220°C after 30 minutes, keep the temperature and pressure for 1.5 hours, release the pressure in the autoclave and raise the temperature in the autoclave to 260°C; react for about 1 hour, add polybutylene glycol with a molecular weight of 2000 into the autoclave, and then add 1 to 3 parts of tetrabutyl titanate to promote esterification reaction, and the reaction is carried out at 280°C and a pressure of 1000 Pa for 3 hours to obtain a polyamide 1212 elastomer; The polyamide 1212 elastomer is placed in an autoclave equipped with a heating jacket and a temperature controller. After the air in the autoclave is replaced by CO2 fluid, the autoclave is filled with CO2 to reach a pressure of 15 MPa and heated to 160-180°C. The temperature and pressure are maintained for 2 hours, and the pressure is quickly reduced to ambient pressure to obtain a polyamide 1212 elastomer low-foam material, which is then crushed to obtain polyamide 1212 elastomer low-foam particles.

2. The elastic bonding coating for preventing aluminum single plate deformation of thermal insulation decorative integrated plate according to claim 1 is characterized by: The flame retardant is a mixture of one or more of aluminum hydroxide, magnesium hydroxide, zinc borate, antimony trioxide, colloidal antimony pentoxide, sodium antimony, ammonium polyphosphate, organic silicon flame retardant, expandable graphite, and dihydroxy metal oxide.

3. The method for preparing the elastic bonding coating for preventing aluminum single plate deformation of the thermal insulation decorative integrated plate according to claim 1 is characterized in that: The steps include: S1: Stirring polyol, catalyst, surfactant, foaming agent, flame retardant and polyamide 1212 elastomer low-foam particles for 1-2 hours to obtain component A; S2: Mix the crude polymerized MDI and the phase change composite material and stir for 1 to 1.5 hours to obtain component B; S3: Mix component A and component B, stir at high speed to make them evenly mixed, spray them on the back of the aluminum veneer, adhere the thermal insulation core material after reaching the specified thickness, and further assemble the thermal insulation decorative integrated panel.

Citation Information

Patent Citations

  • Rock wool heat insulation and decoration integrated board

    CN202416764U

  • Heat preservation and decoration integrated plate system

    CN210918325U

  • Compression-resistant polyurethane foam and preparation method thereof

    CN113292764A

  • High-strength polyamide elastomer material and preparation method thereof

    CN117264203A

  • Ultrahigh-elasticity polyamide elastomer and preparation method thereof

    CN117384375A